2004
DOI: 10.1002/j.2161-0045.2004.tb00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Realized Potential or Lost Talent: High School Variables and Bachelor's Degree Completion

Abstract: This study examined how background and high school variables affected participants in either realizing their potential by completing a bachelor's degree or experiencing lost talent by not completing a bachelor's degree. A sample of participants who had demonstrated above average cognitive ability and had high postsecondary educational goals when in 8th grade was selected from the National Education Longitudinal Study of 1988 (national longitudinal data from 1988 to 2000; National Education, 2002). Several back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 9 publications
3
48
0
1
Order By: Relevance
“…Several student demographic factors have been linked with poor achievement and negative school environments, including poverty (Evans, 2004;Oates, 2003;Trusty & Niles, 2004), race/ethnicity (Signer & Saldana, 2001;Sladen, 1982), and gender. This study found that school counselors who perceived students as being low academic achievers were significantly less likely to rate them as attractive clients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several student demographic factors have been linked with poor achievement and negative school environments, including poverty (Evans, 2004;Oates, 2003;Trusty & Niles, 2004), race/ethnicity (Signer & Saldana, 2001;Sladen, 1982), and gender. This study found that school counselors who perceived students as being low academic achievers were significantly less likely to rate them as attractive clients.…”
Section: Discussionmentioning
confidence: 98%
“…Recent journal articles (Bemak & Chung, 2005;Brinson, Brew, & Denby, 2008;Trusty & Niles, 2004), texts (Liu, 2010;Pederson & Carey, 2003), and professional codes and standards (American School Counselor Association [ASCA], 2005; Council for Accreditation of Counseling and Related Educational Programs [CACREP], 2001) abound with references to the underprivileged, poverty, socioeconomic indicators, and achievement gaps. Much of the empirical evidence relating to social class and school counseling has focused on student self-reported experiences or developmental outcomes (Ackerman, Brown, & Izard, 2004;Rosenbloom & Way, 2004).…”
mentioning
confidence: 96%
“…Kao (2002) found that children were more likely to maintain their educational expectations over time if parents and children share the same expectations. Analyzing NELS data from 1988 to 2000, Trusty and Niles (2004) also found that students with high expectations were more likely to fulfill their goals if their parents also held high expectations for them.…”
Section: Agreement and Disagreement Between Parents' And Children's Ementioning
confidence: 94%
“…Research defines educated employees as those individuals who hold at least bachelor's degrees. These degrees are necessary for entry into many higher paying occupations after the academic credentials an individual has obtained [16,17,18].…”
Section: Literature Review/theoretical Frameworkmentioning
confidence: 99%